KEPUTUSAN PEMBELIAN IPHONE DI WILAYAH KECAMATAN CIPAYUNG - Farhaddina Shella Nabilah, (2020)
Based on data from kompas.com and IDC research on 2019 shows iPhone placed the third position with 11,7% of market share in the world. Unfortunately, this indicates that iPhone gets low purchase decision in smartphone market. Therefore, the purpose of this research is to know, analyze, and prove whether there is any impact from its quality product, price, and promotion to purchase decision. This research applies quantitative method with iPhone users in Cipayung sub-district as its population. Sampels are taken by random sampling method and distributing questionnaire to collect the data. Data is analyzed by descriptive and inferential analysis techniques. SmartPLS 3.0 (Partial Least Square) is used in this research as statistical tool."Result of this research shows that product quality impacts purchase decision"as well as price and promotion, in Cipayung sub-district.